Molecular Characterization of Enterocytozoon bieneusi in Wild Carnivores in Spain. (22nd December 2017) - Santín, Mónica; Calero‐Bernal, Rafael; Carmena, David; Mateo, Marta; Balseiro, Ana; Barral, Marta; Lima Barbero, José Francisco; Habela, Miguel Ángel
Abstract: Microsporidia comprises a diverse group of obligate intracellular parasites that infect a broad range of invertebrates and vertebrates. Among Microsporidia, Enterocytozoon bieneusi is the most frequently detected species in humans and animals worldwide bringing into question the possible role of animal reservoirs in the epidemiology of this pathogen. Although E. bieneusi is an emerging zoonotic pathogen able to infect many domestic and wild mammals that could act as reservoir of infection for humans and other animals, only few studies have documented its occurrence in wild carnivores. To determine the occurrence of E. bieneusi in wild carnivores, we examined 190 wild carnivores collected from different locations in Spain. Twenty‐five fecal samples (13.2%) from three host species (European badger, beech marten, and red fox) were E. bieneusi ‐positive by PCR. Nucleotide sequence analysis of the ITS region revealed a high degree of genetic diversity with a total of eight distinct genotypes including four known (PtEbIX, S5, S9, and WildBoar3) and four novel (EbCar1‐EbCar4) genotypes identified. Phylogenetic analysis showed that the four novel genotypes (EbCar1‐EbCar4), S5, S9, and WildBoar3 clustered within the previously designated zoonotic Group 1. Our results demonstrate that human‐pathogenic genotypes are present in wild carnivores, corroborating their potential role as a source of human infection and environmental contamination.